Menganalisis Majas Perumpamaan yang Terkandung dalam Puisi Cinta Karya : Sapardi Djoko Damono - Fatimatul Jahro; Katharina Woli Namang (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This research aims to describe the Majas parables contained in Love Poems by: Sapardi Djoko Damono. This research uses a descriptive qualitative approach, this research is included in the category of content analysis research. The results of this study indicate that Sapardi likens simple love to the relationship between wood and fire. Wood burned by fire is willing to become ashes without complaint, showing love that is full of sacrifice and sincerity. This parable illustrates that true love does not require great expressions, but real actions and simplicity.